PHYSICOCHEMICAL AND NUTRITIVE CHARACTERIZATION OF HIGH VALUE NONCONVENTIONAL OIL FROM SEEDS OF AMARANTHUS HYBRIDUS LINN - Diemeleou, Chantal A.; Zoue, Lessoy T.; Niamke, Sebastien L. (European Scientific Journal, ESJ, 2014)
This work was carried out to investigate the physicochemical and nutritional properties of oil extracted from seeds of Amaranthus hybridus, an important leafy vegetable of Côte d’Ivoire. The oil yield of Amaranthus hybridus seeds was 9.76 ± 0.74%. Physicochemical properties of extracted oil were as follow: specific gravity (0.92 ± 0.01), refractive index (1.47 ± 0.00), colour lovibond (20.2 ± 0.00), viscosity at 20°C (52.05 ± 0.15 mPas), cloud point (- 2.1 ± 0.00°C) acid value (2.81 ± 0.00 mg KOH/g), peroxide value (5.67 ± 0.58 meq O2/kg), iodine value (119.85 ± 1.22 g I2/100g), saponification value (160.82 ± 3.24 mg KOH/g). Biochemical and nutritive analysis have revealed the following assets: impurities (0.014 ± 0.00%), unsaponifiable matter (2.57 ± 0.21%), phosphorus (0.098 ± 0.01 mg/g), vitamin A (0.44 ± 0.01 mg/g) and vitamin E (0.25 ± 0.01 mg/g). Fatty acids profile of Amaranthus hybridus seed oil highlighted oleic and linoleic acids as major fatty acids with amounts of 36.45 and 33.16 ± 0.01%, respectively. All these interesting characteristics should arouse attention for the usage of Amaranthus hybridus seed oil in food and pharmaceutical industries.